Sustainable Infrastructure Legal Policy in Indonesia: A National Strategic Project Approach for National Development - Maret Priyanta; Cut Sabina Anasya Zulkarnain (Faculty of Law, Sriwijaya University, Indonesia, 2023)
Infrastructure development is the top priority of the Indonesian government. The development of transportation network infrastructure is expected to support the growth of national and international economies by connecting regions and opening public and commodity access. The new integrated growth cities were developed to reduce the burden of Jakarta as the central government and economic national centre. Legal aspects become one of the main issues in realising government politics in developing infrastructure. The national strategic project approach became a mechanism to connect a new development centre, such as the Metropolitan Bandung Area, through infrastructure development. However, its implementation requires a legal and regulatory basis with various technical, social, and economic considerations, including anticipating its environmental impact. This research paper aims to give an academic review of the problem of infrastructure development in Indonesia. The normative legal approach is based on the law's theory, concepts, and principles by considering the technical aspects to develop alternative solutions to provide legal certainty in developing infrastructure in Indonesia. The rules for spatial planning are a key issue in developing infrastructure related to random locations and land acquisition. This conflict becomes a major obstacle in developing new primate cities in Indonesia.